FEATURES OF THE FINANCIAL AND TAX ACCOUNTING OF THE VALUE ADDED TAX IN THE TRANSITION TO THE SIMPLIFIED TAXATION SYSTEM IN THE CONDITIONS OF MARITAL STATE IN UKRAINE - OVDII, Olena; REDZIUK, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article. To systematize changes, innovations and peculiarities of financial and tax accounting of VAT during the transition to a simplified taxation system in the conditions of martial law in Ukraine. The following research methods were used for the purposes of the research: content analysis, comparative analysis, and logical generalization methods were used by the authors to formulate the chosen topic and purpose of the research, critical analysis of scientific and specialized literature; the method of scientific abstraction was used in order to highlight the peculiarities of financial and tax accounting in the conditions of martial law; methods of analysis and synthesis, induction and deduction were used to analyze the main changes and innovations in legislation, the impact on the formation of accounting and tax reporting; the method of qualitative comparison was used to highlight the effects of legislative changes on different groups of economic entities The analysis of changes and innovations in the financial and tax accounting of VAT made it possible to systematize the features of a simplified taxation system, which has a number of advantages over the usual form of taxation, namely: a reduction in the tax burden on enterprises that worked on a single tax system (3% of income + payment of VAT or 5% of income), up to 2%. However, those legal entities and sole proprietorships that supplied goods, works and services taxed at a zero rate do not belong to the above; deferment to the VAT payer for up to 6 months, after the cancellation of martial law, submission of reports, payment of tax and registration of PN/RK in a single register of tax invoices; introduction of preferential VAT rates, namely 7%, for enterprises engaged in the import and sale of fuel and oil products in the domestic market of Ukraine; suspension of fines and penalties both for enterprises and organizations that have not timely paid or submitted relevant reporting documents, and for the state for late reimbursement of VAT from the country’s budget. The obtained research results, compared to similar ones, contain selected changes and innovations, appropriately systematized by the authors. The proposed systematization of changes and innovations in the financial and tax accounting of VAT in relation to the application of a simplified taxation system can be useful both for scientists and specialists who deal with this issue, and for teachers and students of HEI specialty 071 "Accounting and taxation".